Inhibition of PPARγ during rat pregnancy causes intrauterine growth restriction and attenuation of uterine vasodilation - Gokina, Natalia I.; Chan, Siu-Lung; Chapman, Abbie C.; Oppenheimer, Karen; Jetton, Thomas; Cipolla, Marilyn J. (Frontiers in Physiology, 2013)
Decreased peroxisome proliferator-activated receptor gamma (PPARγ) activity is thought to have a major role in preeclampsia through abnormal placental development. However, the role of PPARγ in adaptation of the uteroplacental vasculature that may lead to placental hypoperfusion and fetal growth restriction during pregnancy is not known. Here, pregnant Sprague-Dawley rats (n=11/group) were treated during the second half of pregnancy with the PPARγ inhibitor GW9662 (10 mg/kg/day in food) or vehicle. Pregnancy outcome and PPARγ mRNA, vasodilation and structural remodeling were determined in maternal uterine and mesenteric arteries. PPARγ was expressed in uterine vascular tissue of both non-pregnant and pregnant rats with 2-fold greater expression in radial vs. main uterine arteries. PPARγ mRNA levels were significantly higher in uterine compared to mesenteric arteries. GW9662 treatment during pregnancy did not affect maternal physiology (body weight, glucose, blood pressure), mesenteric artery vasodilation or structural remodeling of uterine and mesenteric vessels. Inhibition of PPARγ for the last 10 days of gestation caused decreased fetal weights on both day 20 and 21 of gestation that was associated with impaired vasodilation of radial uterine arteries in response to acetylcholine and sodium nitroprusside. These results define an essential role of PPARγ in the control of uteroplacental vasodilatory function during pregnancy, an important determinant of blood flow to the placenta and fetus. Strategies that target PPARγ activation in the uterine circulation could have important therapeutic potential in treatment of pregnancies complicated by hypertension, diabetes or preeclampsia.